The influence of the creative problem solving learning model on the mathematical problem solving ability of high school students on linear inequations - Sinulingga, Sintya Lestari; Harahap, Amin; Hasibuan, Lily Rohanita (Universitas Islam Negeri Raden Intan Lampung, 2024)
A student's ability to solve math problems is very, very low because in solving math problems, the learning process does not accustom students to think more creatively. This is because the learning process in the teacher's class still applies conventional methods, and the students in the class have not yet achieved scores above the KKM. This study aims to see the Creative Problem Solving learning model as a series of learning in solving and solving problems systematically based on student creativity to produce effective solutions. This research is a quasi-experimental research using purposive sampling technique. The instrument used in this research is a test of the ability to solve mathematical problems in the form of a written test, a result test and an observation sheet on the implementation of the learning process. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. The results of the study show that the mathematics learning of students using the CPS learning model on the ability to solve mathematical problems of students is better than the results of mathematical learning of students who have followed conventional learning which means that there is an influence of creative problem solving learning on the ability to solve mathematical problems of high school students regarding linear inequalities .